Comparative mitogenomics of Cheiracanthium species (Araneae: Cheiracanthiidae) with phylogenetic implication and evolutionary insights - Li,Zhaoyi; Zhang,Feng (PeerJ, 2025)
The genus Cheiracanthium C. L. Koch, 1839 is the most species-rich genus of the family Cheiracanthiidae. Given the unavailability of information on the evolutionary biology and molecular taxonomy of this genus, here we sequenced nine mitochondrial genomes (mitogenomes) of Cheiracanthium species, four of which were fully annotated, and conducted comparative analyses with other well-characterized Araneae mitogenomes. We also provide phylogenetic insights on the genus Cheiracanthium. The circular mitogenomes of the Cheiracanthium contain 37 genes, including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs) and one putative control region (CR). All genes show a high A+T bias, characterized by a negative AT skew and positive GC skew, along with numerous overlapped regions and intergenic spacers. Approximately half of the tRNAs lack TΨC and/or dihydrouracil (DHU) arm and are characterized with unpaired amino acid acceptor arms. Most PCGs used the standard ATN start codons and TAR termination codons. The mitochondrial gene order of Cheiracanthium differs significantly from the putative ancestral gene order (Limulus polyphemus). Our novel phylogenetic analyses infer Cheiracanthiidae to be the sister group of Salticidae in BI analysis, but as sister to the node with Miturgidae, Viridasiidae, Corinnidae, Selenopidae, Salticidae, and Philodromidae in ML analysis. We confirm that Cheiracanthium is paraphyletic, for the first time using molecular phylogenetic approaches, with the earliest divergence estimated at 67 Ma. Our findings enhance our understanding of Cheiracanthium taxonomy and evolution.
Keywords: Cheiracanthiids; Divergence time; Mitochondrial genome; Molecular phylogenetics; Paraphyly